K-State Alumni Association: neat/marketing recent graduate retention analysis - Hobbs, Brittani (Kansas State University, 2010)
The K-State Alumni Association has the highest percentage of graduates in the Big 12 who are members of the association. As a result, there is a strong network of alumni spanning more than 150,000 living alumni internationally and throughout the United States. This project seeks to utilize the relationship management theory to review current marketing strategies and develop new strategies to increase retention rates of alumni to the association after their one free year of membership, a gift provided to undergraduate students by their perspective college. The focus of the relationship management theory is about building personal relationships, which is in line with the K-State Alumni Association’s mission statement, “Enhancing our Kansas State University family through lifelong involvement.” The recommendations were created to assist the efforts of the Alumni Association to continue to reach out to alumni to meet them where they are at by utilizing media and new programs.
Keywords: Alumni; K-State Alumni Association; Recent Graduates; Journalism (0391)